Toxicity of Ocimum basilicum and Ocimum gratissimum Extracts against Main Malaria Vector, Anopheles gambiae (Diptera: Culicidae) in Nigeria - Kayode David Ileke; Jacobs Mobolade Adesina (Tehran University of Medical Sciences, 2019)
Background: Anopheles gambiae (Diptera: Culicidae) transmit malaria parasite that causes malaria fever in humans, causing millions of deaths every year among infants in tropical countries. This study was undertaken to assess the toxicity of Ocimum basilicum and Ocimum gratissimum against pre-adult stages and adult malaria vector, An. gambiae and non-targeted aquatic organism, fingerlings of Clarias garipienus. Methods: Ethalonic extracts of O. basilicum and O. gratissimum were prepared according to the method described by WHO. The larvae and pupae of An. gambiae were exposed to plant extracts for 24h and their mortality was recorded. Toxicity of Ocimum species on non-targeted organism, fingerlings of C. garipienus was also investigated. Results: Ocimum basilicum showed remarkably potency against pre-adult stages and adults An. gambiae causing 100% mortality at 0.4% concentration within 24h of treatment. The LC50 and LC90 of O. basilicum were lower than O. grattisimum in all stages of An. gambiae studied. Ocimum basilicum and O. gratissimum extracts significantly reduced the number of bites by the vector given a range of 72.25% to 81.75% protection. Ocimum species at the tested concentrations did not significantly reduce the number of fingerlings introduced. Conclusion: Ocimum species at the tested concentrations did not significantly reduce the numbers of non-targeted organisms, fingerlings introduced. Therefore, O. basilicum and O. gratissimum could be used to reduce malaria prevalence in the endemic areas of Nigeria as it poses no threat to aquatic organisms.